Samoan Custom and Human Rights: An Indigenous View - VaÃ¡, Unasa LF (Victoria University of Wellington Law Review, 2009)
This article focuses on human rights as seen from the perspective of Samoan custom and social life. It argues that the roots of human rights as understood by Western societies are metaphysical whereas human rights under Samoan culture stem from being born from human parents and, therefore, an heir or suli. While the genesis of rights may be different, the overall understanding of human rights, however, is argued to be the same. The article examines Samoan cultural practices in light of international human rights standards and draws parallels between them. Custom can then be seen as a source of human rights.